On the Elevated Temperature, Tensile Properties of Al-Cu Cast Alloys: Role of Heat Treatment - A. Girgis; A. M. Samuel; H. W. Doty; S. Valtierra; F. H. Samuel (Advances in Materials Science and Engineering)
The present study aims to investigate the mechanical properties of a newly developed aluminum Al-6.5% Cu-based alloy, coded HT200, as well as to determine how these properties can be further improved using grain refinement and heat treatment. As a result, the effects of different heat treatments and alloying additions on the ambient and high-temperature tensile properties were examined. Three alloys were selected for this study: (i) the base HT200 alloy (coded A), (ii) the base HT200 alloy containing 0.15% Ti + 0.15% Zr (coded B), and (iii) the base HT200 alloy containing 0.15% Ti + 0.15% Zr + 0.5%Ag (coded C). The properties of the three HT200 alloys were compared with those of 319 and 356 alloys (coded D and E, respectively), subjected to the same heat treatment conditions. The results obtained show the optimum high-temperature tensile properties and Q-values for the five alloys of interest, along with the corresponding heat treatment conditions associated with these properties. It was found that the T6 heat-treated alloy B was the optimum alloy in terms of properties obtained, with values comparable to those of commercial B319.0 and A356.0 alloys.